Intraoperative blood loss and the need for preoperative blood preparations in transgender women undergoing facial feminization surgeries: implications for surgeons. Issue 1 (January 2023) - Mahmoud, R.; Arbel, S.; Shuster, A.; Ianculovici, C.; Peleg, O.; Kleinman, S.
Abstract: The aim of this retrospective study was to assess blood loss during facial feminization surgeries and to evaluate blood transfusion requirements. Data from the medical records of all male-to-female transgender patients (transwomen) treated with gender affirming hormones and undergoing facial feminization surgeries were analysed. The total blood loss was calculated based on the haemoglobin balanced method. Twenty transwomen (average age of 25.9 years) were enrolled. Group 1 included 10 transwomen who underwent cranioplasty, genioplasty, and mandibular angles refining, group 2 included six transwomen who underwent cranioplasty and genioplasty, and group 3 included four transwomen who underwent mandibular angles refining and genioplasty. The median calculated blood loss for groups 1, 2, and 3 was 1159.7 ml, 828.5 ml, and 546.2 ml, respectively. The group differences in surgical time, intraoperative fluid amounts, and calculated blood loss volumes were significant. None of the patients required an intraoperative blood transfusion and the hormonal treatment had no effect on the amount of calculated blood loss. Hence, blood loss during facial feminization surgeries is well controlled and does not lead to life-threatening events, precluding the possibility of providing generalized recommendations for preoperative blood transfusion preparations.